PENILAIAN DAYA TARIK DAN PENGEMBANGAN OBJEK WISATA PANTAI TANJUNG BELANDANG DI KABUPATEN KETAPANG - nuri, Jai; Muin, Sudirman; Suci Wulandari, Reine (JURNAL HUTAN LESTARI, 2014)
Tanjung Belandang beach is an area which have potential and attractiveness as a tourist attraction. Natural tourist attraction located in area Tanjung Belandang beach which supported with existence of infrastructure, accommodation, accessibility, and so should be improved development especially if viewed from aspects of tourism. The method used is survey method with descriptive and used interview techniques with instrument a questionnaire. Analysis of data using analysis of Regional Operations GuidelinesÂ  and Nature Attractions Directorate General PHKA 2003 and SWOT Analysis. The result showed rating attraction tourism object Tanjung Belandang beach have value 491,22. After compared with the classification of business development of nature tourism, an area Tanjung Belandang beach have valuation medium (B). This means potential developed into a tourist attraction. Based on assessment for tourism development strategy Tanjung Belandang beach are in quadrant III (WO Strategy) is to maximize opportunities and minimize the threats that exist. As for the points for WO strategy namely: a. Increasing interest tourists to the marine tourism and need to improve the infrastructure supporting tourism facilities; b. Located close to the city center streets in tourist attraction areas need to be improved to provide comfort for visitors; c. Development of tourism as banana boat we need to prepare human resources capable to manage; d. Improve the facilities and infrastructure to support marine tourism; e. Need the support of local government in the development of marine tourism; f. Regional government must make policies to improve facilities and infrastructure so as to attract investor to invest. Keywords: Tourist attraction, nature tourism, beach, Tanjung Belandang